α1-Antitrypsin phenotypes and associated serum protein concentrations in a large clinical population - Bornhorst, Joshua A; Greene, Dina N; Ashwood, Edward R; Grenache, David G (Chest, 2013)
α1-Antitrypsin (AAT) deficiency variants reduce the concentration of serum AAT protease inhibitor and can lead to the development of pulmonary and hepatic disease. Relative frequencies of rare AAT variant phenotypes (non-M, Z, and S) and associated serum concentrations in the clinical population have not been thoroughly described. Protein phenotypes were determined by isoelectric focusing electrophoresis for 72,229 consecutive samples. Phenotype frequencies, median serum concentrations, and central 95% concentration intervals were determined for observed phenotypes. Concurrent AAT phenotype and concentration data were used to evaluate the efficacy of using serum AAT concentration alone to detect AAT deficiency. Age, race, and sex had only slight effects on the median 95% serum protein concentration intervals of the 58,087 PiMM (wild type) phenotype specimens. Positive predictive values were calculated for the detection of potential deficiency phenotypes at different serum cutoff concentrations, aiding potential screening effort design. For example, the PiZZ deficiency phenotype (n = 814) could be detected at 99.5% sensitivity and 96.5% specificity using a cutoff of ≤ 85 mg/dL. However, at-risk specimens with two putative deleterious variants (Z, S, I, F, P, T, and Null variants) were detected with only 85.9% sensitivity at this cutoff (n = 1,661). Rare phenotype variants were observed in 2.5% of samples. This analysis provides novel information on serum AAT concentrations associated with different AAT phenotypes and provides insight into the severity of depression of AAT concentration in the presence of rare deficiency variants. Additionally, it allows for evaluation of efficacy of testing algorithms incorporating AAT serum concentration determination.